TANTANGAN & DINAMIKA POLITIK GENDER DI DUNIA ISLAM: ANALISIS KOMPARATIF MESIR, TURKI, DAN ARAB SAUDI - Kadriyah, Siti Maryamah; Aziz, Abdul; Siti Maryamah Kadriyah; Abdul Azis (JURNAL TAPIS, 2024)
This research focuses on gender politics in the Islamic world. The discussion of gender politics is limited to the feminist movement in three countries: Egypt, Turkey, and Saudi Arabia. Therefore, this study uses a political theory framework to explore the implementation of power-seeking or biased policies. Gender theory discusses the position of Egyptian, Turkish, and Saudi Arabian women in the public sphere in fulfilling gender-just rights and obligations. Elite theory aims to understand government policies for society, especially women. This study uses qualitative research methods, using observation and library data collection techniques. The results show that various obstacles are encountered in the process of gender political struggles in Islamic countries. However, women's political struggles also receive support from various parties, of course, after going through a long struggle. Thus, Egypt, Turkey, and Saudi Arabia are now countries with women's movements that show progress and can be compared with other Islamic countries.